(untitled) (Costa Rican Journal of Guidance & Counseling, 2023)
Polyvagal Theory (PVT) is an innovative contribution to the regulation of emotions and well-being promotion; it helps to understand three types of responses to daily experiences and to distinguish the thoughts, emotions, behaviors, and bodily sensations that characterize each of them. This article discusses the concepts of this theory and how they can contribute to the professional Guidance counselor, both professionally and personally. The work emphasizes how essential interpersonal connections are in regulating emotions, performance in different areas, health, and well-being in general. The importance of the PVT in Guidance is heightened. Finally, reference is made to strategies inspired by PVT.